The Knowledge and Practices of Handwashing Among Street Food Vendors in the Keetmanshoop Municipal Area: none - Namukwambi, Rauna Ndalila; Tuhadeleni, Olivia; Van Neel, Rewaldo (Jour Med Resh and Health Sci, 2022)
Background: Foods sold in the streets are easily accessible and affordable. This makes many people consume these foods regardless of considering some health aspects, especially in developing countries where safe drinking water remains inaccessible to millions of people. However, this results in food vending being a vector of foodborne diseases. Hence handwashing knowledge and practices among street food vendors remain crucial in preventing foodborne illnesses. Based on this background, this study determines the knowledge and practices of street food vendors regarding hand hygiene around the Keetmanshoop municipal area. Setting of the study: The study took place in Keetmanshoop Municipal area Method: A quantitative, descriptive was used to collect information regarding the knowledge and practices of handwashing among street food vendors in the Keetmanshoop municipal area. Data was collected from twenty-two street food vendors using a self-administered questionnaire. Data were analysed manually because the sample size was small. Results: The findings indicated that street food vendors in the Keetmanshoop municipal area range from fair to good knowledge on hand hygiene. However, their hand hygiene practices fall short of standard requirements. Conclusion: It was concluded that there is a need to provide regular training to street food vendors on handwashing practices. Equally, it must be a mandatory requirement for all street food vendors to have handwashing equipment when selling food in the streets. In the same vein, local authorities are advised to develop training materials on hand hygiene and formulate by-laws to ensure compliance to hand hygiene practices among street food vendors. Moreover, the study recommended that the municipality and department of health should conduct compulsory food hand hygiene training for all the existing street food vendors. This must also be the standard requirement for the renewal of trading license and also for those applying to trade as street food vendors. Furthermore, it is recommendable for all street food vendors to have a bucket of water with a tap for handwashing both for themselves and their customers. Lastly, the municipality should do bi-annual supervision of all the street food vendors to ensure that they adhere to hand hygiene practices.